2021
DOI: 10.1002/jpen.2106
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition care practice patterns for patients with COVID‐19—A preliminary report

Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a respiratory virus that poses risks to the nutritional status and survival of infected patients, yet there is paucity of data to inform evidence-based quality care. Methods: We collected data on the nutrition care provided to patients with Coronavirus disease 2019 (COVID-19) by Registered Dietitian Nutritionists (RDNs). Results: Hospitalized COVID-19 patients (N=101) in this cohort were older adults and had elevated body mass index (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 6 publications
1
14
0
1
Order By: Relevance
“…It has been reported that active intervention by a nutritionist/dietitian would be meaningful for patients in the ICU [35], and they might contribute directly to patients' nutrition care or to influence nutrition therapy provided by critical care teams. Their importance has been also reported in less severely ill patients and for prevention of COVID-19 [36,37]. Specialists for nutrition therapy might be needed for active critical care nutrition support.…”
Section: Discussionmentioning
confidence: 96%
“…It has been reported that active intervention by a nutritionist/dietitian would be meaningful for patients in the ICU [35], and they might contribute directly to patients' nutrition care or to influence nutrition therapy provided by critical care teams. Their importance has been also reported in less severely ill patients and for prevention of COVID-19 [36,37]. Specialists for nutrition therapy might be needed for active critical care nutrition support.…”
Section: Discussionmentioning
confidence: 96%
“…The observed increase in prescribed enteral nutrition from 2020 to 2021 may be, among other causes, due to the increase in malnutrition and need for enteral nutritional support in all age groups as infection increases in the population [ 23 , 24 ]. Patients who are hospitalized with COVID-19 have a higher prevalence of malnutrition than their hospitalized counterparts without COVID-19 [ 25 ]. The parallelism of the prescription of containers and healthcare expenditure is notable, with no significant differences in total costs from 2016 to 2021, as it was not seen either during the previous study [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many of them received awake prone therapy, and may potentially suffer from dyspnoea, anosmia and ageusia, which may lead to poor oral intake. 15 EN was started on day 4 of ICU admission in most of these patients. Although they had significantly lower disease severity, their mortality rate was significantly higher than patients first exposed to EN in the initial 2 days of ICU admission.…”
Section: Timing and Feeding Routementioning
confidence: 99%